Service Integration to Enhance Research Data Management: RSpace Electronic Laboratory Notebook Case Study - Stuart Macdonald; Rory Macneil (International Journal of Digital Curation, 2015)
Research Data Management (RDM) provides a framework that supports researchers and their data throughout the course of their research and is increasingly regarded as one of the essential areas of responsible conduct of research. New tools and infrastructures make possible the generation of large volumes of digital research data in a myriad of formats. This facilitates new ways to analyse, share and reuse these outputs, with libraries, IT services and other service units within academic institutions working together with the research community to develop RDM infrastructures to curate and preserve this type of research output and make them re-usable for future generations. Working on the principle that a rationalised and continuous flow of data between systems and across institutional boundaries is one of the core goals of information management, this paper will highlight service integration via Electronic Laboratory Notebooks (ELN), which streamline research data workflows, result in efficiency gains for researchers, research administrators and other stakeholders, and ultimately enhance the RDM process.